1998
DOI: 10.1097/00005392-199804000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Survival of Black Americans With Testicular Cancer

Abstract: Black men had significantly decreased (z <0.02) 5-year disease specific survival, which was 17% less than white patients. The difference in disease specific survival for Hispanic men was not statistically significant. This review of 215 patients with testicular cancer revealed no differences in tumor type or stage at presentation for white, black or Hispanic men. However, a review of these data suggests that disease specific survival outcomes are more ominous in black men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In contrast, Bridges et al found no significant difference in the clinical stages at presentation between Caucasians and non-Caucasians; however, they did found that 5-year disease-specific survival was significantly decreased in non-Caucasians. 9 Fossa et al also found that nonCaucasian race was associated with worse testicular cancerespecific mortality among men with nonseminomas. In addition, they also found that diagnosis at later age was associated with worse outcomes, 18 which is similar to the finding by Moul et al who reported a significant racial disparity in the delay to diagnosis.…”
Section: Commentmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, Bridges et al found no significant difference in the clinical stages at presentation between Caucasians and non-Caucasians; however, they did found that 5-year disease-specific survival was significantly decreased in non-Caucasians. 9 Fossa et al also found that nonCaucasian race was associated with worse testicular cancerespecific mortality among men with nonseminomas. In addition, they also found that diagnosis at later age was associated with worse outcomes, 18 which is similar to the finding by Moul et al who reported a significant racial disparity in the delay to diagnosis.…”
Section: Commentmentioning
confidence: 92%
“…7 In addition, a significant disparity in cancer-specific mortality between Caucasian and non-Caucasian races has been shown. [8][9][10] This has been hypothesized to be attributable to cancer biology, access to health care, socioeconomic factors, baseline comorbidities, and health care literacy. [11][12][13][14] Although studies have identified this disparity, none have studied whether this disparity has changed over time.…”
mentioning
confidence: 99%
“…Approximately one fourth of students believed that each of the following age groups was most at risk for testicular 16 Of the participants, 6% were unsure if women can get testicular cancer; 2% said women can. See Figure 3 for students' recognition of risk factors for testicular cancer.…”
Section: Knowledge Of Testicular Cancermentioning
confidence: 99%
“…In multiple tumor sites, African‐American race represents a risk factor for more advanced stage at diagnosis, more aggressive disease characteristics, and more unfavorable treatment outcomes 1‐11. Among patients with testicular cancer, few reports have examined the effect of race on disease stage and treatment outcomes 12‐16…”
mentioning
confidence: 99%
“…Of the studies that did investigate race, 3 examined survival, which represents the ultimate treatment outcome for any tumor site 12‐14. All 3 studies demonstrated that African‐American race was associated with worse survival in patients who were diagnosed with testicular cancer.…”
mentioning
confidence: 99%